Development of a handheld sensorized needle guide for ultrasound-guided breast biopsy - Real, António Ferreira (2021)
One in every eight women will get breast cancer during their lifetime. Therefore, the early diagnosis of the lesions is fundamental to improve the chances of recovery. To find breast cancers, breast screening using techniques such as mammography and ultrasound (US) imaging scans are often used. When a lesion is found, a breast biopsy is performed to extract a tissue sample for analysis. The breast biopsy is usually assisted by an US to identify the lesion and guide the needle to its location. However, the identification of the needle tip in US image is challenging, requiring great skill from the radiologist. This issue can lead to increased procedure time, multiple puncture attempts and complications such as scarring. To solve these challenges researchers have been developing robotic solutions to automatically detect and target the lesions by using robotic manipulators. However, these robots can be expensive and of difficult adoption for clinics. This work presents a handheld sensorized needle guide attached to the US probe that combines the concepts of robotics and needle guides in a single device. This device aligns the biopsy needle with the US beam’s plane, thus improving needle visibility in the US image as well as estimating the needle tip’s position by means of angle and displacement sensors. This simple handheld device also has the advantage of being low cost and the radiologist is fully in control of the procedure. In a first phase it is intended to select the sensors for the passive robot that estimates the needle tip’s location and using a test setup, device experiments to validate that their precision and accuracy is adequate for the task. In a second phase, simulations will be carried out to evaluate different mechanical configurations of the needle guide and, after prototype construction, validate the precision of the estimated needle tip’s location. In a third phase a more refined prototype is constructed based on the previous results. As a result of this project, it is intended to reduce the risks associated with puncture during breast biopsy and increase the radiologist’s confidence. Tests performed on the sensors have shown they have adequate precision for integration in the needle guide. Finally, the tests performed in the assembled needle guides have shown they have low errors, comparable to those of other robotic solutions in the literature.